FREQUENCY ANALISYS OF RADIAL VELOCITIES VARIATIONS OF XZ CYG - Vasilyeva, S. V. (Одеські астрономічні публікації, 2017)
The observation of RR Lyr type star XZ Cyg were carried out at 50" telescope of Crimean Astrophysical observatory and covered the time interval of JD 2441483 - 2441579. For radial velocities measuring were used H, CaII and other metals line of low dispersion spectrograms. The frequency analysis was carried out using computer code FOUR-1 (Andronov I.L., Odessa Astron. Publ., 1994, 7, 49). Radial velocities variations are sufficiently fitted by sinusoid. The variations of radial velocities with the phase of curve lights and of Blazko effect was investigated.